PROSES AFIKSASI MORFOLOGI ISM (NOMINA) DALAM BAHASA ARAB - Lailatul Zuhriyah; Ahmad Sholihuddin; Muhammad Thohir (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
Arabic is a language full of polymorphism. Where Arabic verbs have an inflectional form and derivative of agglutinative type. This study aims to analyze and explore various types of isim (nouns) in Arabic, which has various affixation variations. Various forms of Arabic word processing give rise to various meanings. This research is library research with qualitative approach and descriptive syncronic method. The findings of this study resulted that the variety of affixation isim (nouns) can be formed from verbs and adjectives with the addition of letters. The affixing process can occur early / prefix (as-sabiq), infixs / insertion (ziyadah), and confixs / prefix and suffixs (as-saabiq wa al-laahiq). The addition of the affixes of the prefix verbs, and the base of the hamzah prefixes, of the adjectiva and verb infix using alif letters, from the noun base consist of suffix ya 'syaddah, alif-nun confixs, nun-wawu, nun-ya' and nun-alif-ta'. Basic verb conjunction with mim-alif, mim-ta' and mim-wawu. Meanwhile, the conceivable meanings include isim alat, isim maf’ul, isim faa’il, isim makan, dan isim zaman.